Average channel capacity of free-space optical mimo systems over atmospheric turbulence channels - Trung, Ha Duyen (ASEAN engineering journal)
In this paper, we theoretically analyze the performance of multiple-input multiple-output (MIMO) free-space optical (FSO) systems. The MIMO/FSO average channel capacity (ACC), which is expressed in terms of average spectral efficiency (ASE) is derived taking into account the atmospheric turbulence effects on the MIMO/FSO channel. They are modeled by log-normal and the gamma-gamma distributions for the cases of weak-to-strong turbulence conditions. We quantitatively discuss the influence of turbulence strength, link distance, and different MIMO configurations on the system ASE. Numerical and computer simulation results are presented in order to verify the validity of the mathematical analysis.